MARITIME INTERCEPTION ON FOREIGN VESSELS CARRYING REFUGEES AND ASYLUM SEEKERS: A VIOLATION OF UNCLOS AND NON-REFOULEMENT PRINCIPLE? - Mizalfia Nursabrina (Padjadjaran Journal of International Law, 2020)
AbstractEach state has the right to protect their national security in every possible way, and illegal acts such as aliens entering their territory without permit is no exception. They implement regulations and policies to prevent people smuggling, including but not limited to maritime interception towards vessels under suspicion of carrying refugees and asylum seekers. Yet, in the implementation, human rights violations tend to happen towards the passengers. This study aims to analyze the legality of maritime interception on foreign vessels carrying refugee and asylum seekers, and whether the said conduct raised issues of state responsibility. This study was conducted by analyzing relevant international law instruments and principles such as non-refoulement and state responsibility. The analysis comes to the conclusion that states have certain jurisdiction to conduct interception operations at sea with the means of protecting their national security. Should the act of interception be proven to inflict threats of danger towards the lives of the intercepted refugees and asylum seekers, states should be held responsible for the damage bared to the refugees and asylum seekers. In conducting maritime interceptions, states should ensure the refugee identity of the intercepted vessel’s passengers and should seek that they are entitled to international protection. Keywords: Maritime Interception, Principle of Non-Refoulement, State Responsibility AbstrakSetiap negara mempunyai hak untuk melindungi keamanan nasionalnya dengan berbagai macam cara, dan tindakan ilegal seperti warga negara asing memasuki wilayah suatu negara tanpa izin bukan merupakan pengecualian. Negara-negara telah menetapkan seperangkat peraturan dan kebijakan untuk mencegah penyelundupan manusia, termasuk namun tidak terbatas pada pencegatan kapal di wilayah laut yang dicurigai mengangkut para pengungsi dan pencari suaka. Namun, dalam pelaksanaannya tindakan pencegatan seringkali menimbulkan pelanggaran hak asasi manusia kepada para penumpang kapal. Penelitian ini bertujuan untuk menganalisis legalitas pencegatan kapal yang mengangkut pengungsi dan pencari suaka. Penelitian ini dilaksanakan dengan menganalisa hukum internasional yang berkaitan. Penelitian ini menunjukan bahwa negara mempunyai yurisdiksi tertentu untuk melaksanakan pencegatan di laut dengan tujuan untuk mempertahankan keamanan nasional. Selain itu, negara harus bertanggung jawab atas kerugian yang dialami oleh para pengungsi dan pencari suaka selaku penumpang kapal yang dicegat apabila pencegatan tersebut menimbulkan ancaman bagi hidup mereka. Dalam melaksanakan pencegatan di wilayah laut, negara-negara harus memastikan identitas para penumpang kapal yang dicegat, dan memberikan perlindungan internasional bagi mereka yang berstatus sebagai pengungsi dan pencari suaka. Kata Kunci: Pencegatan Wilayah Laut, Prinsip Non-Refoulement, Tanggung Jawab Negara